Nevtrini iz vesolja - Dobravec, Anja (Matrika, 2014)
First I will present the basic characteristics of neutrino particles and describe where and how they are created. I will continue with the description of the Solar neutrino problem which has been solved with the theory of neutrino oscillations. Finally I will describe the methods of detecting neutrinos and show the point of exploring neutrinos.
Keywords: detection; detekcija nevtrinov; jedrske reakcije; neutrinos; nevtrini; nuclear reactions; supernovae; supernove